(untitled) (Research, Society and Development, 2024)
Mast cell tumors are the most common malignant neoplasms in dogs, with variable biological behavior, demonstrating great relevance in small animal medicine and veterinary oncology due to their high prevalence and variable clinical evolution. The objective of this study was to describe the clinical case of a Golden Retriever canine, which presented an increase in volume in the facial region, resulting in the diagnosis of mastocyma; highlighting the etiology, pathophysiology, epidemiological aspects, diagnosis, treatment, and prognosis of the disease. The cytological examination by FNA (fine needle aspiration) revealed a diagnosis of cutaneous mast cell tumor; where surgery was indicated to excise the neoplastic change, the submandibular lymph node, sending the material for histopathological diagnosis and immunohistochemistry to obtain a prognostic marker that revealed cutaneous mast cell tumor, Grade II, Low grade. The patient was treated with antihistamines, famotidine, clinical monitoring and no chemotherapy protocol was necessary; since low-grade cutaneous mast cell tumors tend to behave better and local therapy may be curative.